Respuestas

¡La mejor respuesta!
2013-01-09T19:52:47+01:00

5x/x-4 + 1= 4/x+3

 

5x+x-4=4(x-4)/x+3

 

(6x-4)(x+3)=4(x-4)

 

6x^2+18x-4x-12=4x-16

6x^2+10x+4=0

 

3x ----------+ 2

 

2x-----------+ 2

 

(3x+2)(2x+2)=0

3x+2=0      ;     2x+2=0

x=-2/3         ;      x=-1

 

SALUDOS

 

2013-01-09T20:06:40+01:00

5x+x-4=4(x-4)/x+3

 

(6x-4)(x+3)=4(x-4)

 

6x^2+18x-4x-12=4x-16

6x^2+10x+4=0

 

3x....+ 2

 

2x....+ 2

 

(3x+2)(2x+2)=0

3x+2=0      ;     2x+2=0

x=-2/3         ;      x=-1